Prominent places on the landscape: Occupations at Cowhead Mesa along the eastern escarpment edge of the Southern High Plains of Texas. (2nd January 2017) - Hurst, Stance; Johnson, Eileen
Abstract : Cowhead Mesa is located along the eastern escarpment of the Southern High Plains near Post, Texas. Survey and excavation on top of the mesa have uncovered evidence for multiple occupations that span at least 3000 years. Multiple occupations on highpoints and rock art incised into the sandstone walls, marks Cowhead Mesa as a significant place on the landscape. We performed prominence and viewshed analyses using geographical information systems to determine the topographic uniqueness of Cowhead Mesa. Results indicate Cowhead Mesa was chosen as a place to inscribe rock art due to its prominence within the river valley and view of the surrounding landscape. Feature and artifact analyses suggest Cowhead Mesa also served as a short-term camp site and was an important stopping point as hunter-gatherer groups moved across the Southern Plains.